Prevalence and risk factors of Rift Valley fever in humans and animals from Kabale district in Southwestern Uganda, 2016. - Luke Nyakarahuka; Annabelle de St Maurice; Lawrence Purpura; Elizabeth Ervin; Stephen Balinandi; Alex Tumusiime; Jackson Kyondo; Sophia Mulei; Patrick Tusiime; Julius Lutwama; John D Klena; Shelley Brown; et al. (Public Library of Science (PLoS), 2018)
Rift Valley fever (RVF) is a zoonotic disease caused by Rift Valley fever virus (RVFV) found in Africa and the Middle East. Outbreaks can cause extensive morbidity and mortality in humans and livestock. Following the diagnosis of two acute human RVF cases in Kabale district, Uganda, we conducted a serosurvey to estimate RVFV seroprevalence in humans and livestock and to identify associated risk factors.Humans and animals at abattoirs and villages in Kabale district were sampled. Persons were interviewed about RVFV exposure risk factors. Human blood was tested for anti-RVFV IgM and IgG, and animal blood for anti-RVFV IgG.655 human and 1051 animal blood samples were collected. Anti-RVFV IgG was detected in 78 (12%) human samples; 3 human samples (0.5%) had detectable IgM only, and 7 (1%) had both IgM and IgG. Of the 10 IgM-positive persons, 2 samples were positive for RVFV by PCR, confirming recent infection. Odds of RVFV seropositivity were greater in participants who were butchers (odds ratio [OR] 5.1; 95% confidence interval [95% CI]: 1.7-15.1) and those who reported handling raw meat (OR 3.4; 95% CI 1.2-9.8). No persons under age 20 were RVFV seropositive. The overall animal seropositivity was 13%, with 27% of cattle, 7% of goats, and 4% of sheep seropositive. In a multivariate logistic regression, cattle species (OR 9.1; 95% CI 4.1-20.5), adult age (OR 3.0; 95% CI 1.6-5.6), and female sex (OR 2.1; 95%CI 1.0-4.3) were significantly associated with animal seropositivity. Individual human seropositivity was significantly associated with animal seropositivity by subcounty after adjusting for sex, age, and occupation (p < 0.05).Although no RVF cases had been detected in Uganda from 1968 to March 2016, our study suggests that RVFV has been circulating undetected in both humans and animals living in and around Kabale district. RVFV seropositivity in humans was associated with occupation, suggesting that the primary mode of RVFV transmission to humans in Kabale district could be through contact with animal blood or body fluids.